Remnant cholesterol and suicide attempts in untreated first-episode major depressive disorder - Xu, Ping; Fan, Cheng; Yan, Mingxing; Liu, Junjun; Zhang, Xiangyang (Frontiers in Psychiatry, 2025)
ObjectiveThe objective of this research was to investigate the relationship between remnant cholesterol (RC) levels and suicide attempts (SA) made by Chinese patients with untreated first-episode major depressive disorder (UFE MDD).MethodsThis study included 1718 patients with UFE MDD. Demographic, clinical characteristics, and blood lipid parameters were collected. The 17-item Hamilton Depression Rating Scale (HAMD), the 14-item Hamilton Anxiety Rating Scale (HAMA), and the positive subscale of the Positive and Negative Syndrome Scale (PANSS) were used to assess their depression, anxiety, and psychotic symptoms, respectively. Multivariable binary logistic regression analysis was used to estimate the association between RC and the risk of SA. A two-piecewise linear regression model was used to investigate the threshold effects if non-linear associations existed.ResultsUnivariate logistic regression analysis showed a significant positive correlation between RC and SA, but after controlling for confounding factors, the association between them was not statistically significant. After dividing the RC into quartiles, only the RC in the Q4 group was significantly positively correlated with suicide attempts (OR = 1.73, 95% CI: 1.13-2.65, P = 0.012, vs. Q1) in a fully adjusted model. Curve fitting analysis also showed a nonlinear relationship between RC and suicide attempts with an inflection point at 1.99 mmol/L in RC. On the left of the inflection point, a significant positive correlation was observed between RC and SA (OR: 1.36, 95% CI: 1.09-1.69, p=0.006). However, on the right of the inflection point, no significant correlation was found (OR: 0.79, 95% CI: 0.55-1.14, p=0.214).ConclusionThis study demonstrates a non-linear association between RC levels and SA in patients with untreated first-episode major depressive disorder. When RC was less than 1.99 mmol/L, they showed a significant positive correlation.